Strategi Keuangan UMKM Untuk Bertahan dan Berkembang UMKM Binaan Rumah BUMN Yogyakarta - Putra, Okta Eka; Musadat, Irfan Achmad; Pramayuda, Agung; Mahendra, Rivan Yusni; Fikri, Andri Muhammad (Jaanur Elbarik Indonesia, 2025)
This community service activity aims to enhance the managerial capacity of MSMEs fostered by Rumah BUMN Yogyakarta, particularly in financial management and the utilization of digital technology. MSMEs face various challenges, including poor financial recordkeeping, limited financial literacy, and unpreparedness in responding to market changes. The program is designed to strengthen business resilience and sustainability through training in basic financial recording, budgeting, the use of digital financial applications, and assistance in developing business strategies. Using a descriptive qualitative and participatory approach, the activity involves observation, interviews, and hands-on practice with business actors. The results show a significant improvement in participants’ understanding of financial management and digitalization, as well as their ability to use financial applications such as BukuWarung. Furthermore, continuous communication between MSMEs and Rumah BUMN has been established, creating a support ecosystem for business growth. This intervention has successfully laid a strategic foundation for MSMEs in developing adaptive and responsive business sustainability plans in the face of digital challenges. It is recommended that similar programs be replicated on a broader scale with more intensive and sustainable mentoring